The Influence Quality Products and Quality Service to Satisfaction Consumer Indihome in Bekasi - M. Fairuz Najmuddin Adya; Zumrotul Fitriyah (PT Inovasi Pratama Internasional, 2023)
The objective of this research is to assess the impact of independent variables, namely service quality and product quality, on customer happiness with Indihome goods in the Bekasi region. The study intends to examine the correlation between the dependent variables and customer satisfaction. The study was carried out on individuals living in the Bekasi region who utilized Indihome products. A total of 112 individuals were included in this research, employing a purposive sampling strategy. The data collection method employed in this research involved the distribution of questionnaires. The sample criteria for this study were individuals who are Indihome users living in Bekasi, have been using Indihome services for a minimum of one year, and are at least 17 years of age. The present study used the partial least squares (PLS) analysis technique. The conducted analysis reveals that there exists a favorable correlation between product quality and customer happiness. The positive impact of service quality on customer satisfaction is evident.